A conditional Berry–Esseen inequality. (March 2019) - Klein, Thierry; Lagnoux, Agnés; Petit, Pierre
Abstract: As an extension of a central limit theorem established by Svante Janson, we prove a Berry–Esseen inequality for a sum of independent and identically distributed random variables conditioned by a sum of independent and identically distributed integer-valued random variables.